Chemical exchange saturation transfer fingerprinting for exchange rate quantification. Issue 4 (30th May 2018) - Zhou, Zhengwei; Han, Pei; Zhou, Bill; Christodoulou, Anthony G.; Shaw, Jaime L.; Deng, Zixin; Li, Debiao
Abstract : Purpose: There is an increased interest to determine the exchange rate using CEST to provide pH information. However, current CEST quantification methods require lengthy scan times and do not address magnetization transfer effects. The purpose of this work was to apply the magnetic resonance fingerprinting (MRF) concept to CEST to achieve more efficient and accurate exchange rate quantification. Methods: The proposed CEST fingerprinting method used varying saturation powers and saturation times to create unique signal evolutions for different exchange rates. The acquired signal was matched to a predefined dictionary to determine the exchange rate. The magnetization transfer effects were also addressed in the framework of CEST fingerprinting: The simulated dictionary could predict the signal curves without magnetization transfer effects, and comparing the dictionary to the acquired signals allowed the correction of the magnetization transfer effects. The CEST fingerprinting method was compared with the conventional pulsed quantitative CEST method using omega plots in the creatine phantom study. Results: The CEST fingerprinting method has a significantly reduced scan time (10 minutes versus 50 minutes) while providing more accurate exchange rate quantification using literature values as the reference. Conclusion: In this study, we demonstrate that CEST fingerprinting is more efficient (5 times faster) compared with pulsed quantitative CEST. It is also shown that the results of the proposed CEST fingerprinting technique are much closer to the literature values than pulsed quantitative CEST at 3 T.